2017
DOI: 10.1097/mph.0000000000000916
|View full text |Cite
|
Sign up to set email alerts
|

Critically Ill Children With Hemophagocytic Lymphohistiocytosis: A Case Series of 14 Patients

Abstract: Children with hemophagocytic lymphohistiocytosis (HLH) are at an increased risk of critical illness. In this study, we described the clinical characteristics of critically ill children with HLH and identify factors associated with poor clinical outcomes. Children who were diagnosed with HLH with emergent admission to Children's Intensive Care Unit (CICU) between January 1, 2000 and October 31, 2015 were included. The primary outcome was CICU mortality. Over the 15-year period, there were 14 critically ill pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 23 publications
0
34
2
Order By: Relevance
“…It is mentioned in the literature that the disease has no predilection for gender. Leow et al, presented 14 children with HLH, among whom eight (57.1%) were male (10). Based on the obtained results of the current study, the male to female ratio was 1.8:1 (55% male), which was inconsistent with the previous studies.…”
Section: Discussioncontrasting
confidence: 94%
“…It is mentioned in the literature that the disease has no predilection for gender. Leow et al, presented 14 children with HLH, among whom eight (57.1%) were male (10). Based on the obtained results of the current study, the male to female ratio was 1.8:1 (55% male), which was inconsistent with the previous studies.…”
Section: Discussioncontrasting
confidence: 94%
“…Patients with HLH (pediatric and adult) stand out as some of the most critically ill patients in the ICU . While HLH can be very difficult to discern from typical sepsis or multiple organ dysfunction syndrome (MODS), there are often clues that the severity of inflammation may be more than expected for critical illness and further investigation for possible HLH needs to be considered.…”
Section: Typical and Unusual Hlh Presentation Phenotypesmentioning
confidence: 99%
“…While HLH can be very difficult to discern from typical sepsis or multiple organ dysfunction syndrome (MODS), there are often clues that the severity of inflammation may be more than expected for critical illness and further investigation for possible HLH needs to be considered. These patients tend to be persistently febrile with significant cytopenias, especially thrombocytopenia, and require multiple transfusions . Hypofibrinogenemia may be helpful to discern HLH from sepsis, though disseminated intravascular coagulation (DIC) may lead to a similar appearance .…”
Section: Typical and Unusual Hlh Presentation Phenotypesmentioning
confidence: 99%
“…Numerous studies reported over half of deaths occur within 30 days after SHLH diagnosis due to MODS or second infection [14,15]. Leow et al [16], assessed poor prognostic factors and mortality for pediatric patients with HLH admitted to the cardiac ICU, they found patients with a higher mortality index score at admission, higher serum lactate levels, the need for mechanical ventilation, vasoactives and CRRT were associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%